2008
DOI: 10.1152/ajpregu.00398.2007
|View full text |Cite
|
Sign up to set email alerts
|

Survival dependency of intramuscular ICC on vagal afferent nerves in the cat esophagus

Abstract: cells of Cajal (ICC) have been proposed as stretch receptors for vagal afferent nerves in the stomach based on immunohistochemical studies. The aim of the present study was to use electron microscopy and the anterograde degeneration technique to investigate ultrastructural features and survival dependency of ICC associated with vagal afferent innervation of the cat esophagus. This is the first report on the ultrastructural characteristics of ICC in the cat esophagus. Intramuscular ICC (ICC-IM) were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Previous observations have indicated that IMA varicosities contacting ICCs form synapse-like contacts (vesicles, prejunctional thickenings, etc.) with ICCs (Powley et al, 2008; see also Huizinga et al, 2008), and the present observations now illustrate how numerous such varicosities are (see, for example, Figures 1, 2 and 3). The extensive numbers of contact sites of IMAs with ICCs underscore the possibility that IMAs may carry stretch or length signals that originate or are transduced within the ICC-muscle-fiber apparatus of the gut (Huizinga et al, 2010).…”
Section: 1 Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Previous observations have indicated that IMA varicosities contacting ICCs form synapse-like contacts (vesicles, prejunctional thickenings, etc.) with ICCs (Powley et al, 2008; see also Huizinga et al, 2008), and the present observations now illustrate how numerous such varicosities are (see, for example, Figures 1, 2 and 3). The extensive numbers of contact sites of IMAs with ICCs underscore the possibility that IMAs may carry stretch or length signals that originate or are transduced within the ICC-muscle-fiber apparatus of the gut (Huizinga et al, 2010).…”
Section: 1 Discussionsupporting
confidence: 77%
“…Since small bundles of heterogeneous axons run in proximity to ICCs (e.g., Gabella, 1989; Mitsui and Komuro, 2002; Huizinga et al, 2008) and since we observed--in a recent ultrastructural study that included tracer-labeled IMAs--these bundles frequently contain only one or two IMA fibers and several axons unlabeled with dextran (Powley et al, 2008; also see Figures 4A and 5A), we evaluated a series of specimens in which IMAs were labeled with dextran, or ICCs were processed for c-Kit, and immunohistochemistry was used to identify CGRP+ neurites.…”
Section: 1 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A morphometric analysis revealed an equally significant decrease in the density of CD117-IR ICCs in both groups of individuals infected, with and without megaesophagus (Figure 4). and differentiation of ICCs [32], the denervation process may be one of multiple causal factors that lead to ICCs loss in the esophagus of T. cruzi infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…6 and 5B; also see Powley and Phillips, 2011). Furthermore, IMA-ICC associations have also been examined ultrastructurally, and IMA varicosities form synapse-like contacts (i.e., the varicosities of the IMA branches exhibit prejunctional thickenings and contain vesicles) with ICCs (Powley et al, 2008; see also Huizinga et al, 2008). In addition, both of these nonneural elements of the muscularis externa, i.e., ICC-IMs and smooth muscle, that complex with IMAs express mechanoreceptive channels (Mazet, 2015).…”
Section: Functions Of Gastric Imasmentioning
confidence: 99%